A qualitative case study of constructivist teaching at a high school in a northern area of Vietnam - Oanh, Pham Thi Kieu; Van-Trao, Nguyen; Thi Mai, Nguyen Huong (Institute of Advanced Engineering and Science, 2025)
This study aims to identify the English high school teachers’ beliefs at a high school in the northern region of Vietnam regarding constructivist teaching (CT) and their actual classroom practices (CP). This paper summarizes results from a five-year Ph.D. study conducted with seven high-school English teachers within a qualitative case study research design with the help of three data collection instruments, including semi-structured and Stimulated recall interviews and direct classroom observations. Thematic analysis using MAXQDA was chosen for data analysis. The findings uncovered themes that emerged from the data, which might lay the foundation for classifying teachers into three groups: adaptive originators (AOs), neutral pragmatists (NPs), and traditional conservers (TCs). Most TCs’ teaching philosophies were teacher-centered and supportive of conventional teaching techniques. Still, the NPs acknowledged that instructional strategies needed to be changed. The AOs sought to change how teachers used CT; they actively put strategy into place to bring about meaningful change. These results were valuable references for high school teachers to assist their students with better constructivist instruction, thus enhancing the quality of teaching and learning English in the 4.0 era.